THE ROLE OF SOCIAL MEDIA IN BUILDING BRAND AND ENHANCING CUSTOMER ENGAGEMENT FOR YOUNG ENTREPRENEURS: A LITERATURE REVIEW - Johan Manurung; Ritha F. Dalimunthe; Prihatin Lumbanraja (Cahaya Ilmu Bangsa, 2024)
Social media plays a crucial role in strengthening the position of young entrepreneurs in an increasingly competitive market. No longer just an additional tool, social media has become a strategic necessity in building a strong brand and fostering meaningful customer engagement. Through these platforms, young entrepreneurs can achieve several strategic objectives, including increasing political awareness, expanding customer knowledge about products, and enhancing meaningful interactions with customers. Effective marketing strategies are required to fully leverage the potential of social media in achieving desired business goals, making it a strong foundation for building sustainable brands in this increasingly digital business environment. The methodology used in this study is descriptive qualitative, where researchers rely on various literature to obtain research data and use a qualitative approach because the data produced are in the form of words or descriptions.